Estudio de caso a una Persona con alteración de tromboembolismo pulmonar y neumonía. - Palomino-Salazar, Francisca Liliana (Universidad de Sonora, 2019)
This case study was performed in critically ill adults with medical diagnosis of pulmonary thromboembolism submassive type I and community-acquired pneumonia, treated at the General Hospital of the State of Sonora. Evaluating functional patterns of Marjorie Gordon was used and supplemented with additional scales. Was used elaborated nursing diagnoses based on the NANDA Nursing Diagnoses Classification (NOC) and the Classification of Nursing Interventions (NIC) in care planning to perform. Clinical reasoning allows the application of relevant knowledge and assessment techniques, diagnostic and problem handling a patient. Therefore, from the above a care plan prioritizing the most affected needs and make individualized interventions was performed.